Tingkat Kedisiplinan Atlet Taekwondo - Yogi Setiawan; Nurul Ihsan; Masrun Masrun; Fachrizal Ambia (Departemen Kesehatan Dan Rekreasi Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2025)
The problem in this study is that the discipline of Taekwondo Dojang UNP athletes is unknown. The purpose of this study is to determine the discipline of Taekwondo Dojang UNP athletes. This study is classified as a descriptive research type. The population in this study was athletes at Dojang UNP, totaling 30 people. Sampling using the Total Sampling technique, so the sample in this study amounted to 30 people. The instrument used was a questionnaire. Analysis of research data used a frequency distribution technique with a percentage calculation of P = F / N x 100%. Research results: the level of discipline of Taekwondo Dojang UNP athletes was 87.59% in the very high category. Referring to the results of this study, which states that the level of discipline of Taekwondo Dojang UNP athletes is included in the discipline category.